Preventing displacement, addressing root causes and the promise of the Global Compact on Refugees - Türk, V (Refugee Studies Centre, University of Oxford, 2019)
Preventing displacement by addressing its root causes requires a holistic approach and engagement by a wide range of actors. The starting point must be a better understanding of root causes and their complexity.